(untitled) (2011)
Carbon steel samples were buried in loamy soil modified with lime, fly-ash and Portland cement in ratio of 5 and 10% during 60 days. Corrosion attack was assessed by electrochemical impedance spectroscopy. Loamy soil without modification was taken as reference. The corrosion products in rust were characterized by Raman spectroscopy. It was found that soil with fly-ash and Portland cement can develop corrosion protection to bare steel due to the changing of formed rust on steel samples. Lepidocrocite and Goethite were found as major constituents in formed rust on buried steel in soil modified with fly-ash and cement, while Magnetite was found in formed rust on buried steel in soil without addition of cementitious materials and modified with lime. According to the electrochemical results, the soil with 5% of fly-ash exhibited the anticorrosive best performance.